University Level Curriculum and Entrepreneurial Intentions among Nepali Business Students: Examining the Mediating Role of Teaching Methods - Subedi, Dhruba Prasad; Bhandari, Dilli Ram (Nepalese Journal of Management and Technology, 2024)
Entrepreneurship education at the university level plays a crucial role in shaping students’ entrepreneurial intentions and capabilities. This study investigates the relationship between university-level curriculum and entrepreneurial intentions among Nepalese Management students along with the mediating role of teaching methods. To achieve the stated objective, data were collected from the primary source using a structured questionnaire administered through convenience sampling. The respondents comprised 390 undergraduate and graduate-level management students studying at colleges affiliated to Tribhuvan and Pokhara Universities in the Kathmandu Valley. The SmartPLS 4.0 was used to analyze the structural relationships within the proposed theoretical model. The findings of this study validated the set hypotheses that university level curriculum has positive significant effect on entrepreneurial intentions among Nepalese Management students. Additionally, integration of experiential learning, problem-based learning, case studies, access to entrepreneurial role models and success stories in the curriculum positively influences students’ entrepreneurial aspirations and universities can more effectively prepare students for entrepreneurial endeavors. The study highlighted the significance of designing curricula and selecting teaching approaches that nurture entrepreneurial mindsets, thereby better preparing students for entrepreneurial opportunities in changing economy of Nepal. The findings indicate that to enhance entrepreneurial skills among management students, it is crucial to create entrepreneurial-friendly curricula and employ appropriate teaching methods tailored to meet the specific needs of aspiring entrepreneurs.